Original paper"Migraine side effect" and stroke recurrence in late follow-up after transcatheter patent foramen ovale closure as secondary prevention of cryptogenic thromboembolism - Kumor, Magdalena; Biernacka, Elżbieta K.; Demkow, Marcin; Konka, Marek; Płatek, Anna E.; Jagodzińska, Michalina; Hoffman, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction : Patent foramen ovale (PFO) is associated with cryptogenic strokes, recurrent transient neurologic deficits, sleep apnea, decompression illness and migraines with aura. Aim : We verify cryptogenic embolism recurrence after transcatheter PFO closure in patients younger than 55 years old, and determine the prevalence of migraine with aura before and after PFO closure. Material and methods: We sent a questionnaire concerning the recurrence of stroke or transient ischemic attack (TIA) and the presence of migraine symptoms before and after PFO closure to 224 consecutive patients (mean age 40.9 ±9 years; 103 men; 108 patients < 40 years old, 116 patients 40–55 years old) after successful PFO transcatheter closure as secondary prevention of cryptogenic embolism. Results : The mean follow-up period was 37.8 ±32.5 (median 27) months. Stroke or TIA recurred in 6 patients (2.6%), all of whom were over 40 years old at the time of closure. The median time of recurrence was 24 months. Two patients (0.89%) died, but the deaths were not related to the device nor to thromboembolism. Migraine occurred in the study group before closure in 68 (30.4%) patients. After the procedure 55 (80.9%) reported improvement or disappearance of migraine symptoms. Conclusions : Recurrent strokes after PFO closure are rare, and they occur more often in patients over 40 years old at the time of closure. The PFO closure results in migraine subsiding or symptoms noticeably ameliorating.